MEDICAL EDUCATION: STRATEGIES FOR INTEGRATING TRADITIONAL AND DIGITAL METHODS - Abdujalilova Feruza Milimamatovna (Innovate Conferences, 2025)
The use of 3D digital models in anatomy education enhances students’ comprehension and their ability to visually perceive complex structures compared to traditional methods. This study analyzed the effectiveness of using these models in the learning process, as well as the opportunities for practical skills development and cognitive growth through interactive technologies. The results demonstrated that digital models play a significant role in deepening anatomical understanding and increasing student engagement.
Keywords: Anatomy, 3D models, digital education, medical education, interactive technology.